Embedding the three pass protocol messages into transmission control protocol header - Suherman Suherman; Deddy Dikmawanto; Syafruddin Hasan; Marwan Al-Akaidi (Institute of Advanced Engineering and Science, 2021)
Transmission control protocol provides reliable communication between two or more parties. Each transmitted packet is acknowledged to make sure successful deliveries. Transport layer security protocols send security information exchange as TCP loads. As results, the handshaking stage experiences longer delay as TCP acknowledgement process has already been delay prone. Furthermore, the security message transfers may have their own risks as they are not well protected yet. This paper proposes TCP-embedded three pass protocol for dynamic key exchange. The key exchange is embedded into TCP headers so that transmission delay is reduced, and message transfer is secured. The proposed protocol was assessed on self network by using socket programming in lossless environment. The assessments showed that the proposed protocol reduced three-pass protocol message transfer delay up to 25.8% on lossless channel. The assessment on security also showed that TCP-embedded three pass protocol successfully secured each transmitted TCP load using a unique key; that is much securer than the compared method.